2003
DOI: 10.1034/j.1399-0039.2003.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DRB1, DQB1 and DPB1 polymorphism in the Naxi ethnic group of South‐western China

Abstract: Polymorphism of HLA‐DRB1, DQB1 and DPB1 was revealed with a sequencing‐based typing (SBT) method in unrelated healthy volunteers from the Naxi ethnic group. Among the 43 DRB1 alleles detected, the most common allele was DRB1*12021 with a frequency of 17%, followed by DRB1*08032, DRB1*09012 and DRB1*1404 with frequencies of 8.5%, 7.4% and 7.4%, respectively. Among 23 DQB1 alleles detected, the most frequent DQB1 allele was DQB1*03011/0309 (21.9%), followed by DQB1*0502 (16.4%) and DQB1*05031 (9.6%). For the DPB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 12 publications
4
25
0
Order By: Relevance
“…The majority of studies have shown that the DPB1 locus is not under a balancing selection, and that heterozygosity in HLA antigens is providing selective advantage. The present study has shown that homozygosity for DPB1 locus does not differ significantly from the value expected under neutrality, which is in concordance with other previously published results (Fu et al ., 2003).…”
Section: Introductionsupporting
confidence: 94%
See 1 more Smart Citation
“…The majority of studies have shown that the DPB1 locus is not under a balancing selection, and that heterozygosity in HLA antigens is providing selective advantage. The present study has shown that homozygosity for DPB1 locus does not differ significantly from the value expected under neutrality, which is in concordance with other previously published results (Fu et al ., 2003).…”
Section: Introductionsupporting
confidence: 94%
“…A phylogenetic tree based on the allelic frequency of the DPB1 gene was constructed by the neighbour‐joining (NJ) method with mega 2 software (Kumar et al ., 2001). Data on HLA‐DPB1 allele frequencies of other 13 populations, including Naxi (Fu et al ., 2003), Yao (Chen et al ., 1993), Pumi (Liu et al ., 2002), Yi (Fei et al ., 1993), Guangdong Han (Falco et al ., 1993), Man (Geng et al ., 1995), Shenyang Han (Yu et al ., 1995), Hubei Han (Gong et al ., 1999), Uygur (Mizuki et al ., 1998), Jing, Li, Dulong and Lahu (Xu et al , unpublished data), were collected for phylogenetic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The result of the homozygosity F ‐test is shown in Table 2. There was no significant difference between the observed and the expected F , so the neutrality selection in the HLA‐DPB1 gene of the Nu population could not be rejected, which is consistent with other previously published results (Fu et al ., 2003; Hu et al ., 2005a). Therefore, we can speculate the evolutionary relationship among ethnic groups by the frequencies of alleles among various ethnic populations.…”
Section: Introductionsupporting
confidence: 91%
“…A phylogenetic tree based on the allelic frequency of the DPB1 gene was constructed by the neighbour‐joining (NJ) method with mega 2 software (Kumar et al ., 2001). Data on HLA DPB1 allele frequencies of other 28 populations, including Guangdong Hans (Falco et al ., 1993), Hunan Hans (Zhang & Guo, 1994), Shenyang Hans (Yu et al ., 1995), Naxis (Fu et al ., 2003), Pumis (Liu et al ., 2002), Yis (Fei et al ., 1993), Lisus (Hu et al ., 2005), Tibetans (Li et al ., 1999), Mans (Geng et al ., 1995), Jings (Lin et al ., 2003), Dais (Fan et al ., 1992), Taiwanese (Zimdahl et al ., 1999), South Koreans (Song et al ., 2002), Japanese, Indonesians, Tuvas, N. Europeans, Gambians, Cameroonians (Begovich et al ., 2001), Singapore Chinese (Imanshi et al ., 1991), Svans (Sanchez‐Velasco & Leyva‐Cobian, 2001), Russians (Kapustin et al ., 2002), Slovakians (Cechova et al ., 1998), Greeks (Papassavas et al ., 2000), French (Bera et al ., 2001), Gabonese (Migot‐Nabias et al ., 1999), Pygmies, and Congolese (Renquin et al ., 2001), were used for phylogenetic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore their offspring, such as the Yi studied here, inherited more genetic characteristics from the NEA. Thus our study, combined with previous research [29,31] and historical and archaeologic records, provides some valuable evidence for understanding the history of the TBs. …”
Section: Discussionmentioning
confidence: 86%